Answer:
x > 19
Step-by-step explanation:
2(x+x+12) > 100
2(2x+12) > 100
4x+24 > 100
4x > 76
x > 19
Answer:
Simplifying
4u = 10.24
Solving
4u = 10.24
Solving for variable 'u'.
Move all terms containing u to the left, all other terms to the right.
Divide each side by '4'.
u = 2.56
Simplifying
u = 2.56
Step-by-step explanation:
(b). → Simplify: [{5^(x-+1) + 5^x}/{6×5^x}]
= [{5^(x+1+x)}/{6×5^x}]
= [{5^(2x+1)}/{6×5^x}]
= [{5^(2x+1)}/{6×5^x}]
= [{5^(2x+1-x)}/6]
= [{5^(x+1)}/6]Ans.
(c). 4a³b²
= 4(3)³(-2)²
Since, a = 3 and b = -2.
so,
= 4(3*3*3)(-2*-2)
= 4(27)(4)
= 108(4)
= 432Ans.
<u>also</u><u> </u><u>read</u><u> similar</u><u> questions</u><u>:</u> simplify 6/x-6+3x/x+5-1/(x-6)(x+5)..
brainly.com/question/9027174?referrer
simplify the equation simplify x^5/8/x^1/6..
brainly.com/question/84093?referrer
<span>he geodesics connecting the North and South Poles intersect at both of the Poles</span>
The answer should be F(x)=|x+6|